2006
DOI: 10.1002/elan.200503501
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly Film of Zeolite Y Nanocrystals Loading Palladium on an Au Electrode for Electrochemical Applications

Abstract: Nano-scale zeolite Y crystals were synthesized, and palladium nanoparticles were prepared in the supercage of the zeolite by "ship-in-a-bottle" approach. A novel method to fabricate zeolite-modified electrode (ZME) loading Pd nanoparticles was developed, in which the zeolite Y loading Pd 2þ ions was self-assembled on (3-mercaptopropyl) trimethoxysilane-attached Au surface to form the stable and density packed multilayers (SAM-ZME). The structures of zeolite Y and the SAM-ZME were investigated by using TEM, XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The inclination of the base line for the voltammogram of VSB‐5/CPE and CoVSB‐5 electrodes can be attributed to the additional resistance obtained from the presence of VSB‐5 molecular sieves and the oxidation–reduction process of oxygen species in the molecular sieve layer 30. This inclination in baseline has been reported previously for all electrodes modified with aluminosilicate zeolites 30–32.…”
Section: Resultssupporting
confidence: 76%
“…The inclination of the base line for the voltammogram of VSB‐5/CPE and CoVSB‐5 electrodes can be attributed to the additional resistance obtained from the presence of VSB‐5 molecular sieves and the oxidation–reduction process of oxygen species in the molecular sieve layer 30. This inclination in baseline has been reported previously for all electrodes modified with aluminosilicate zeolites 30–32.…”
Section: Resultssupporting
confidence: 76%
“…It was then reported that the application of pulsed voltage instead of dc voltage was likely to better control the amount of deposited zeolite from sub-monolayer to multilayer [63]. After a pioneering work on covalent attachment of zeolite particles to SnO 2 electrode via a silane coupling agent [64], some related strategies have recently appeared: the covalent self-assembly of zeolite particles on (3-mercaptopropyl)trimethoxysilane-attached gold surface and subsequent silanization of zeolite particles [65], or the controllable arrangement of zeolite/polyelectrolyte multilayers deposited on indium-tinoxide (ITO) electrode by the layer-by-layer (LBL) assembly technique [66,67]. An alternative coupling more or less these two approaches is the silanization of a gold surface with (3-mercaptopropyl)trimethoxysilane, hydrolysis and exposition of this monolayer to a cationic polymer and final contact with zeolites that are immobilized on the polymer film by favorable electrostatic interactions [68].…”
Section: Preparation Of Zmesmentioning
confidence: 98%
“…In the viewpoint of practical applications, more benefits would be expected for Pd-loaded zeolite films and membranes. As a typical example, the film of zeolite-Y loading Pd nanoparticles fabricated via self-assembly on the (3-mercaptopropyl)trimethoxysilane-modified Au electrode exhibited higher electrocatalytic activity for oxidation of adsorbed CO than the pure zeolite-Y film . It has been well recognized that the Pd membranes possess the application potential for hydrogen-selective separation processes. The thin membranes of Pd-loaded zeolites with selective permeability to hydrogen should be advantageous to intensify a hydrogen-related catalytic reaction in the membrane reactor. , …”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of Pd-loaded zeolite membranes can be performed through self-assembling postsynthetic Pd-loaded zeolite crystals . However, the membranes synthesized as such may contain large crystal boundaries, resulting in low separation efficiencies .…”
Section: Introductionmentioning
confidence: 99%